Regional Competitiveness and Strategic Development of Seaweed Cultivation in East Nusa Tenggara - Jackson Kubang (Journal of Economics Business Industry, 2025)
Seaweed represents one of the most economically significant marine commodities in East Nusa Tenggara Province, yet the development potential of the commodity remains unevenly distributed and analytically underdocumented across individual regencies. This study examines the competitive position, production dynamics, development constraints, and strategic priorities of seaweed cultivation across five regencies in East Nusa Tenggara, namely East Flores, Alor, Sikka, Lembata, and East Sumba. The study employs an integrated multi-method framework combining contribution level analysis, Static Location Quotient (SLQ), Dynamic Location Quotient (DLQ), Shift Share Analysis, Strengths Weaknesses Opportunities Threats (SWOT) analysis, and the Analytical Hierarchy Process (AHP). Secondary data on production volume and production value were obtained from the Central Statistics Agency of East Nusa Tenggara and the respective regency Maritime and Fisheries Offices. Primary data were gathered through structured stakeholder interviews organized around four production factors: capital, labor, natural resources, and the business environment. East Flores is the only regency classified as Superior, combining an SLQ of 1.02 with a DLQ of 1.04. Alor and Sikka are classified as Potential, while Lembata and East Sumba are classified as Leading, with East Sumba recording the highest DLQ at 1.67 and a cumulative production growth of 143.52 percent. Shift Share Analysis identifies positive Differential Shift components in East Flores, Lembata, and East Sumba, confirming locally driven competitive advantages. The dominant constraints across all regencies are nature related, including cyclone disruption, ice ice disease pressure, and inadequate post harvest infrastructure. AHP prioritization places drying and processing facility improvement (global weight 0.136) and certified seedling access (0.124) as the two highest strategic priorities. This study is the first to integrate SLQ, DLQ, Shift Share, SWOT, and AHP into a single comparative analytical framework applied to seaweed as a distinct commodity across five regencies in East Nusa Tenggara, generating both a competitive classification and a prioritized development strategy that extends beyond the descriptive outputs of prior single-tool studies.